Coğrafi Bilgi Sistemleri (CBS) Destekli Çok Kriterli Karar Verme Yöntemleri ve Analitik Hiyerarşi Tekniği Kullanarak Uşak Merkez İlçede Alternatif Çöplük Alanlarının Belirlenmesi / Alternative Landfill Site Selection in Uşak District by Using Multi-Criteria Decisionmaking Analysis Supported by Geographical Information Systems (GIS) With Analytic Hierarchy Process - Deniz, Mehmet; Topuz, Mustafa (Journal of History Culture and Art Research, 2018)
Abstract The increasing world population began to concentrate in cities especially after the Industrial Revolution. After the Second World War, societies with over consumption have brought with it the waste problem. In particular, the growth of urban areas, both as a population and as an area, has led to the increase of waste material and the existing landfills located in the border of the city. This situation, which can lead to health consequences, has led local and central governments to find new landfills. When the literature is examined, it has been seen that studies about the subject have been made. In this study, alternative landfill areas were determined in Uşak Central District by using geographical information systems and analytic hierarchy process which is one of the multi criteria decision making methods. The analytical hierarchy process used in the method part is the multi criteria decision making method, which allows to determine the degree of importance based on the Pair-wise comparisons of the determined criteria. In determining the alternative sites, rivers, settlements, lands, faults, landslide, slope, agricultural value of the area, land use type, transportation networks, geological formations, large soil classes and distance to airport were taken into consideration. The maps of the criteria were prepared using ArcMap software. Euclidean distance analysis was applied and reclasify was performed. Distance between settlements and rivers was determined as the most important criteria at the end of the Pair-wise comparisons. Weighted overlay was applied by using weight ratios determined by analytical hierarchy method and alternative sites were determined. As a result of the analysis, six different sites in total 1522 hectares were found suitable near Dışkaya, Taşkonak, Yenişehir, Bağbaşı, Bozköy, Göğem and Karlık villages. The results of the study were limited to GIS analysis. The presence of a dense settlement and stream drenage in the research area has limited the storage space. Öz Artan dünya nüfusu özellikle Sanayi Devriminden sonra şehirlerde yoğunlaşmaya başlamıştır. İkinci Dünya Savaşından sonra aşırı tüketime yönelen toplumlar atık problemini de beraberinde getirmiştir. Özellikle şehirsel alanların hem nüfus hem de alan olarak büyümesi atık madde artışının yanında mevcut çöp depolama alanlarının şehrin içinde kalmasına da neden olmuştur. Sağlığı tehlikeye sokabilen sonuçlara sebep olan bu durum yerel ve merkezi yönetimleri yeni deponi alanları bulmaya itmiştir. Literatür incelendiğinde konu ile ilgili çalışmaların yapıldığı görülmüştür. Bu çalışmada coğrafi bilgi sistemleri ve çok kriterli karar verme yöntemlerinden bir tanesi olan analitik hiyerarşi kullanılarak Uşak Merkez ilçesinde alternatif atık depolama alanı yerleri belirlenmiştir. Yöntem kısmında kullanılan analitik hiyerarşi, belirlenen kriterlerin ikili karşılaştırmalarına dayanan önem derecelerinin belirlenmesini sağlayan ÇKKV yöntemidir. Çalışmada alternatif sahaların belirlenmesinde akarsular, yerleşim alanları, bakı, faylar, heyelan, eğim, sahanın tarımsal değeri, arazi kullanım şekli, ulaşım ağları, jeolojik formasyonları, büyük toprak sınıfları ve havaalanına olan mesafe olmak üzere on iki kriter dikkate alınmıştır. Kriterlerin haritaları ArcMap yazılımı kullanılarak hazırlanmıştır. Çalışmada öklid mesafe analizi uygulanarak yeniden ağırlıklandırma işlemleri yapılmıştır. İkili karşılaştırmalar sonunda yerleşmelere ve akarsulara olan uzaklık en önemli ölçütler olarak belirlenmiştir. Analitik hiyerarşi yöntemi ile belirlenen ağırlık oranları kullanılarak çakıştırma işlemi (weighted overlay) uygulanmış ve alternatif sahalar belirlenmiştir. Analiz sonucunda Dışkaya, Taşkonak, Yenişehir, Bağbaşı, Bozköy, Göğem ve Karlık köyleri yakınlarında toplam 1522 hektarlık altı farklı saha uygun bulunmuştur. Araştırmanın sonuçları CBS analizleri ile sınırlı tutulmuştur. Araştırma sahasında yoğun bir yerleşme ve akarsu ağının bulunması depolama alanı yapılabilecek yerleri sınırlamıştır.